أثر التطور العلمي في الأذان - عيسى زعاترة د.أيمن (Scientific Journal of University of Benghazi, 2026)
The advancement in technology have reached a point where it is possible for people to easily reach each other regardless of distance. However, this is all a gift from "Allah" who taught mankind what otherwise they did not know, and provided them the means to reach such knowledge. It all started with the invention of electricity which provides the needed power for radio stations and enable people to broadcast all over the world in a short period of time. In addition, with the use of electricity, it is possible to amplify sounds many times over using loud speakers.. Muslims have adopted the use of loud speakers to call for the daily prayers (Athan) to reach distance within large towns. Through this research, we are going to address the impact of this scientific development on "Athan", in terms of what is required of the "muethin", and the Sunnah for him, as well as the fate of the second Athan on Friday, and the rightness of Athan unification of Cities in a country, as is the case in some Muslim countries